Verifying the Use of Food Labeling Data for Compiling Branded Food Databases: A Case Study of Sugars in Beverages - Hafner, Edvina; Lavriša, Živa; Hribar, Maša; Krušič, Sanja; Kušar, Anita; Žmitek, Katja; Skrt, Mihaela; Poklar Ulrih, Nataša; Pravst, Igor (Frontiers in Nutrition, 2022)
Attached